Born this way: The effect of an unexpected child benefit at birth on longer-term educational outcomes - Sergi Sánchez-Coll (SERIEs - Journal of the Spanish Economic Association, 2023)
Aiming to boost fertility rates, in 2007 the Spanish government implemented a universal exteuro2500 baby bonus paid to mothers giving birth or adopting a child, leading to a short-lived increase in births. In this study, I measure the causal impact that the transfer had on the language and mathematical competencies of the children of eligible mothers at the end of primary school in the Catalonia region. I do so by taking advantage of how the policy was announced, leading to a sharp regression discontinuity design and a difference-in-discontinuities specification. The subsidy did not improve student achievement at age 12, since in the preferred diff-in-disc specification using the pooled sample of schools we can rule out grade improvements greater than 0.1 standard deviation units with 95% confidence. While some effects in the subsample of boys in disadvantaged schools are large in magnitude, of roughly 0.2-0.41 standard deviation units representing a 4-11% improvement from the average test score, they do not reach statistical significance and are likely caused by the high variability in test scores both before and after the policy implementation rather than by the subsidy itself, as suggested by robustness tests.
Keywords: H31; I38; J13; J24; 330; Baby bonus; Children; Education; Income shock; Natural experiment; Spain